EFL Teacher's Perceptions of Using Flipped Classrooms in Language Teaching for Higher Education - Alsaedi, Buthaynah (Advances in Social Sciences Research Journal, 2024)
The Flipped Classroom in higher education language teaching through the eyes of EFL teachers. The advent of technology in education has led to a change in the way conventional ways of pedagogy have been taught, thus raising questions. The study uses qualitative methods including in-depth interviews, focus group discussions, and reflective narratives, to address different aspects of EFL teachers’ experiences of the flipped classroom approach. Educators are also sampled from different institutions, of different levels of experience, and also with various cultures. The results highlight that EFL instructors’ views and experiences are more contextual. The approach is analyzed with the aim of demonstrating the impact of the approach on the teacher-student relationship, student involvement, as well as the student’s overall experience. In addition, it looks into the implementation issues, showing a way of how an organization or a class may cope with a new teaching philosophy. It also brings out emerging themes such as learner autonomy, technology integration, and a new definition for teachers’ roles in a Flipped Classroom structure. It further examines the cognitive shifts in EFL teachers and the modifications in their teaching methods, evaluation methods, and bespoke learning resources over time. In addition, professional development for teachers and language education programs needs additional support and materials to help them through the complex linguistic environment. The study adds to the literature on innovations in EFL settings, giving policymakers and curriculum developers a basis for improving teaching practice. A detailed examination of the relationship between EFL teachers and the Flipped Classroom model in higher education language teaching is presented in this research. It contributes significantly to the ongoing discussion about the best practices for language education in the digital era by untangling the strands of perceptions, challenges, and adaptations.